Optic nerve head recovery following the intraocular pressure – lowering surgery in the eye with early juvenile glaucoma – nine-year follow-up - Marković, Vujica; Vuković, Dragan; Marjanović, Ivan; Petrović Pajić, Sanja; Radosavljević, Aleksandra; Ilić, Aleksandra; Marić, Vesna; Božić, Marija (Vojnosanitetski pregled, 2020)
Introduction. Congenital uveal ectropion (CEU) is a rare, non-progressive condition often accompanied with eyelid ptosis, anterior insertion of the iris, disgenesis of the irido-corneal angle and glaucoma. Case report. We present a case of a seven-year-old girl with a congential unilateral uveal ectropion and a secondary glaucoma which had daily variations from 13 up to 50 mm Hg. The patient had no other abnormalities of the iris or underlying systemic diseases. Introduced local anti-glaucomatous therapy initially normalized intraocular pressure (IOP), but failed to provide long term normalisation. Trabeculectomy normalized the IOP which resulted in the reduction of the cup/disc ratio and restitution of neuroretinal rim. The rim area increased to 1.716 mm2 (0.958 mm2 preoperative) rim volume, was 0.666 mm3 (0.195 mm3 preoperative) while cup-disc (C/D) ratio decreased to 0.330 (0.626 preoperative) as well as linear C/D=0.574 (0.791 preoperative). Neuroretinal rim (NR) was preoperatively preserved in the Ti segment, damaged in T, Ts, N, Ns segments, and borderline in the Ni segment. Postoperatively, neuroretinal rim was preserved in all segments. Conclusion. In the presented case trabeculectomy induced recovery of the nerve tissue of the optic nerve head which was confirmed by Haidelberg Retina Tomograph II (HRT II). The treatment results have been maintained during the follow-up period of nine years without topical or systemic antiglaucomatous therapy. Although CEU is a non-progressive and benign eye disease, associated glaucoma can cause severe optic nerve damage if not detected early and treated properly. As can be seen in the presented case, an adequate treatment can prevent and even reverse optic disc neuropathy.